2021
DOI: 10.12701/yujm.2020.00234
|View full text |Cite
|
Sign up to set email alerts
|

Association between gestational age at delivery and lymphocyte-monocyte ratio in the routine second trimester complete blood cell count

Abstract: Preterm birth is a major cause of long-term morbidity and mortality in infants. Therefore, there have been many studies about the etiology and pathophysiology of preterm birth and methods for its early prediction and prevention. Complete blood cell (CBC) count parameters including neutrophil-lymphocyte ratio (NLR), lymphocyte-monocyte ratio

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This means there is no statistically significant age difference between the preterm and term labor groups. Previous studies stated no difference in maternal age between the preterm labor groups on the indication, spontaneous, or term preterm labor [20]. The results of this study were also presented by Daglar et al [21] that there is no difference in the mean age of the mother between groups with term labor, the threat of preterm labor, and preterm labor.…”
Section: A Characteristics Of the Research Samplesupporting
confidence: 83%
“…This means there is no statistically significant age difference between the preterm and term labor groups. Previous studies stated no difference in maternal age between the preterm labor groups on the indication, spontaneous, or term preterm labor [20]. The results of this study were also presented by Daglar et al [21] that there is no difference in the mean age of the mother between groups with term labor, the threat of preterm labor, and preterm labor.…”
Section: A Characteristics Of the Research Samplesupporting
confidence: 83%
“…Inflammatory parameters, such as platelet count to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) can be calculated using complete blood count (CBC) test results [12]. The platelet count and indices, including mean platelet volume (MPV), platelet distribution width (PDW) and platelet large cell ratio (P-LCR) from the CBC test provide important information on the occurrence of gestational diabetes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Although there was no significant difference in CBC parameters, Cha et al [34] found that a higher LMR in the second trimester was associated with a lower gestational age at birth. In the present study, in line with the literature, a negative Pearson correlation was found between PLR and NLR and gestational age at birth.…”
Section: Discussionmentioning
confidence: 99%